Spatial planning and decision support system for urban metropolitan planning and monitoring: a case of Klang Valley, Malaysia - Yaakup, Ahris; Muhammad Ludin, Ahmad Nazri; Abu Bakar, Siti Zalina; Sulaiman, Susilawati (2005)
Planning methodology has changed over the years following the shift of emphasis from producing plan, which described a state of affairs expected of some future date, to one acknowledging the continuous and cyclical nature of planning. This necessitates planning be based on the identification of needs and goals, the formulation and evaluation of alternative courses of action and monitoring of adopted programmes. It can be traced that the development of planning support system run parallel from the â€˜databaseâ€™ to â€˜informationâ€™ approach, starting from a focus on applied science in the 1960s through a profound consideration on the political process in the 1970s and to an emphasis on communication in the 1980s. The dynamic nature of planning and monitoring of development in Klang Valley, the fastest growing region in Peninsular Malaysia, apparently requires a â€˜toolâ€™ for continuous evaluation and analysis of current environment as well as the capacity for future development. Apart from managing the comprehensive GIS database, evaluation becomes an essential step in the planning process especially in selecting the appropriate development scenario alternative to be implemented. As such, the concept of Integrated Land use Assessment (ILA) was introduced through the â€œApplication of GIS for Klang Valley Regionâ€? (AGISwlk) project. The ILA model developed is implemented through incorporation with the use of What-if Planning Support System, a scenario-based, policy-oriented planning support system. A user interface is also developed to ease the access and preparation of data from the AGISwlk database to run the ILA model and generate alternative scenarios. The introduction of ILA as an integrated land use planning approach that applies the GIS analysis capabilities while supported by the use of planning support system (What if?) is seen as a good alternative for achieving better and more rational decisions. The methodology was developed and organized based on the GIS spatial analysis process and planning support system framework as well as the identification of policy and strategy to be used as guideline and direction of study in achieving the desired output. The developed model is expected to dynamically support the preparation of the Klang Valley Regional Master Plan.